Sequence of PSE-2 beta-lactamase. - Huovinen, P (1988)
The nucleotide sequence of PSE-2 beta-lactamase, an enzyme that readily hydrolyzes both carbenicillin and oxacillin, has been determined. The deduced sequence of 266 amino acids contained 93 residues identical to those of OXA-2 beta-lactamase and the Ser-Thr-Phe-Lys tetrad also found in the active site of TEM-1 beta-lactamase.